2008
DOI: 10.1158/0008-5472.can-07-5644
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of Breast Cancer Show Preferential Site of Relapse

Abstract: We explored whether the five previously reported molecular subtypes in breast cancer show a preference for organ-specific relapse and searched for molecular pathways involved. The ''intrinsic'' gene list describing the subtypes was used to classify 344 primary breast tumors of lymph node-negative patients. Fisher exact tests were used to determine the association between a tumor subtype and a particular site of distant relapse in these patients who only received local treatment. Modulated genes and pathways we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

59
572
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 708 publications
(638 citation statements)
references
References 36 publications
59
572
1
6
Order By: Relevance
“…In addition, our study demonstrated that different tumor subtypes showed a different tendency to bone metastases. The incidence proportion of bone metastases was highest among patients with the HR‐positive HER2‐negative and HR‐positive HER2‐positive subtypes, which are in accordance with other publications describing the patterns of metastatic breast cancer 11, 12, 36. The multivariable logistic regression indicated that patients with the HR‐positive HER2‐negative subtype had significantly greater odds of having bone metastases at diagnosis than patients with other subtypes, whether among the entire cohort or within the subset with metastatic disease.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, our study demonstrated that different tumor subtypes showed a different tendency to bone metastases. The incidence proportion of bone metastases was highest among patients with the HR‐positive HER2‐negative and HR‐positive HER2‐positive subtypes, which are in accordance with other publications describing the patterns of metastatic breast cancer 11, 12, 36. The multivariable logistic regression indicated that patients with the HR‐positive HER2‐negative subtype had significantly greater odds of having bone metastases at diagnosis than patients with other subtypes, whether among the entire cohort or within the subset with metastatic disease.…”
Section: Discussionsupporting
confidence: 91%
“…Previous findings have confirmed that patients with an HR‐positive status are more likely to have bone metastases than those with HR‐negative status. The absence of WNT/β‐catenin signaling and the involvement of transforming growth factor β and fibroblast growth factor signaling have been found to promote HR‐positive breast cancer metastases to bone 12, 37…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,116 The pattern of metastatic spread of tumors with a basal-like phenotype seems to be different from that of non-basal-like cancers: they are reported to less frequently disseminate to axillary nodes and bones 42,117 and to favor a hematogenous spread, 42,[117][118][119] with a peculiar proclivity to develop metastatic deposits in the brain and lungs. 120 It should be noted that patients with triple-negative and basal-like cancers tend to develop adverse events and die due to disease within the first 5-8 years after diagnosis. After the 8-year mark, the hazard rate for patients with grade 2 or ERpositive cancers is actually higher than that of patients with basal-like cancers.…”
Section: Clinical Behavior Of Basal-like and Triple-negative Breast Cmentioning
confidence: 99%
“…ER-negative breast cancers included the ERBB2+, basal-like and normal-like subtypes. The intrinsic subtypes of breast cancer have clinical relevance [5][6][7], as have gene expression signatures that had been defined based on clinical outcome of breast cancer patients [8][9][10][11]. Importantly, the success of gene expression profiling in breast cancer classification implies a relatively restricted set of recurrent expression patterns among breast cancer subtypes.…”
Section: Introductionmentioning
confidence: 99%